Resources
Testimonials
Plans
Sign in
Sign up
Resources
Testimonials
Plans
AI tutor
Welcome to Bytelearn!
Let’s check out your problem:
Prove that
csc
′
(
x
)
=
−
csc
(
x
)
cot
(
x
)
\csc'(x) = -\csc(x)\cot(x)
csc
′
(
x
)
=
−
csc
(
x
)
cot
(
x
)
View step-by-step help
Home
Math Problems
Algebra 1
Simplify exponential expressions using exponent rules
Full solution
Q.
Prove that
csc
′
(
x
)
=
−
csc
(
x
)
cot
(
x
)
\csc'(x) = -\csc(x)\cot(x)
csc
′
(
x
)
=
−
csc
(
x
)
cot
(
x
)
Start Function Definition:
Step
1
1
1
: Start by writing the function whose derivative we need to find.
\newline
y
=
csc
(
x
)
=
1
sin
(
x
)
y = \csc(x) = \frac{1}{\sin(x)}
y
=
csc
(
x
)
=
s
i
n
(
x
)
1
Apply Chain Rule:
Step
2
2
2
: Use the
chain rule
to differentiate
y
y
y
with respect to
x
x
x
.
y
′
=
−
(
1
sin
2
(
x
)
)
⋅
cos
(
x
)
y' = -\left(\frac{1}{\sin^2(x)}\right) \cdot \cos(x)
y
′
=
−
(
sin
2
(
x
)
1
)
⋅
cos
(
x
)
Simplify Using Identities:
Step
3
3
3
: Simplify the expression using trigonometric identities.
\newline
y
′
=
−
csc
(
x
)
⋅
cot
(
x
)
y' = -\csc(x) \cdot \cot(x)
y
′
=
−
csc
(
x
)
⋅
cot
(
x
)
More problems from Simplify exponential expressions using exponent rules
Question
Evaluate.
\newline
2
2
=
2^2 =
2
2
=
_____
Get tutor help
Posted 1 year ago
Question
Evaluate. Write your answer as a fraction or whole number.
\newline
(
1
4
)
4
(\frac{1}{4})^4
(
4
1
)
4
= _____
Get tutor help
Posted 9 months ago
Question
Which is equal to
9
−
61
9^{-61}
9
−
61
?
Get tutor help
Posted 9 months ago
Question
Simplify.
\newline
Express your answer using positive exponents.
\newline
r
5
⋅
r
8
r^5 \cdot r^8
r
5
⋅
r
8
Get tutor help
Posted 9 months ago
Question
Simplify. Express your answer using a single exponent.
\newline
(
h
2
)
6
(h^2)^6
(
h
2
)
6
\newline
______
Get tutor help
Posted 9 months ago
Question
Simplify. Express your answer using positive exponents.
\newline
(
9
p
5
)
(
5
p
8
)
(9p^5)(5p^8)
(
9
p
5
)
(
5
p
8
)
\newline
_____________
Get tutor help
Posted 9 months ago
Question
Simplify. Express your answer using positive exponents.
\newline
(
2
v
3
)
(
4
v
)
(
5
v
)
(2v^3)(4v)(5v)
(
2
v
3
)
(
4
v
)
(
5
v
)
\newline
______
Get tutor help
Posted 1 year ago
Question
Simplify. Express your answer using a single exponent.
\newline
(
5
z
8
)
2
(5z^8)^2
(
5
z
8
)
2
\newline
_____________
Get tutor help
Posted 9 months ago
Question
Simplify. Express your answer using positive exponents.
\newline
r
9
⋅
r
8
⋅
r
-
5
r^9 \cdot r^8 \cdot r^{\text{-}5}
r
9
⋅
r
8
⋅
r
-
5
\newline
______
Get tutor help
Posted 9 months ago
Question
Which expression is equivalent to
6
×
6
8
6 \times 6^8
6
×
6
8
?
\newline
Choices:
\newline
1
6
9
\frac{1}{6^9}
6
9
1
\newline
6
8
6^8
6
8
\newline
1
6
8
\frac{1}{6^8}
6
8
1
\newline
6
9
6^9
6
9
Get tutor help
Posted 1 year ago
Related topics
Algebra - Order of Operations
Algebra - Distributive Property
`X` and `Y` Axes
Geometry - Scalene Triangle
Common Multiple
Geometry - Quadrant